Humours as a Vehicle for Discussing Women's Sexuality: A Case Study of Talkpod - Ulfa, Chery Narasyah Chiora; Putri, Seffina Nabilla; Pamuji, Indah Ratri Sekar; Chaerunnisya, Rayoeng Dwi; Nurhadi, Muizzu (CV. Era Digital Nusantara, 2024)
This research examines the representation of women's sexuality on social media, with a special focus on Indonesian cultural and religious affects. Traditionally, Indonesian women's sexuality has been strongly shaped by social norms that emphasize sexual purity and modesty. But social media has turned into a double-edged sword, allowing people to express themselves while also fostering objectification and. This study uses descriptive qualitative and Sara Mills' Critical Discourse Analysis to examine the sexual objectification of Pamela Safitri, as woman, at the